PENGARUH PDRB PERKAPITA, TINGKAT SUKU BUNGA TABUNGAN BANK UMUM DAN INFLASI TERHADAP SIMPANAN MASYARAKAT PADA BANK SYARIAH DI KALIMANTAN BARAT - B61108045, Reni Helvira, (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT Islamic Bank has an important role to sustain societies economic in West Borneo. The Islamic banks growth and financial performance in undergoing their intermediation role is supported by the amount of deposit that can be gathered which later it is distributed in the form of loan. This research discusses about the influence of Capita Gross Domestic Regional Product, conventional banks interest rate, and inflation towards Islamic banks deposit in West Borneo. This research is a descriptive study which investigates the condition of Capita Gross Domestic Regional Product, conventional banks interest rate, and inflation so that the effects of those three factors toward Islamic banks deposit in West Borneo can be described completely and accurately. The population of this research is all West Borneo Islamic bank. The data are obtained from Economics Regional Study of Bank Indonesia (KER) and West Borneo Statistic Centre Board (BPS). Data is analyzed by using multiple linier regressions that consist of simultaneous influence test, partial influence test, correlation test and determination coefficient test. Before performing regression test, the data passes classical assumption test which consist of normality, autocorrelation, multicolinearity, and heteroscedastisity. The result of this research shows that Capita Gross Domestic Regional Product, conventional banks interest rate, and inflation simultaneously influence Islamic banks deposit in West Borneo. Partialy, Capita Gross Domestic Regional Product has positive influence; conventional banks interest rate has negative influence, while inflation doesnt have significant influence towards Islamic banks deposit in West Borneo. Keywords: Islamic Banks Deposit, Capita Gross Domestic Regional Product (PDRB), Conventional Banks Interest, and Inflation.